Decomposition of epistemology and decision-making for the era of modern management - Perić, Marko, ekonomist (Array, 2019)
In this paper, the authors describe the essential implications of epistemology for modern management theories in practical situations through the era of historical epistemology as postmodernism and neo–modernism by means of case studies (without individual detailed descriptions). The gender issue is mentioned in epistemology and its approach to change and strategy which renders the paper even more relevant. Moreover, scientific acknowledgement of practical stances, as also the moral paradigm, trigger discussion on applicable solutions in the corporate world for the intermediation of tangible and intangible goods and services. Three main areas of the business cycle are selected to represent three pillars of modern social–economic behaviour as our financial legacy in business and management transformation. In the last section of the paper are listed the reasons for narrow– picking, this being the first step in establishing a business model for a transformational strategy in the era of modern management.